THE APOLOGY STRATEGIES USED BY A BUDGET HOTEL FRONT OFFICERS IN HANDLING CUSTOMER COMPLAINTS - Vivere Talo; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study focused on the use of apology strategies used by female and male front officers to reveal the types of apology strategies used and to reveal the similarities and differences between female and male front officers’ way of apologizing in handling customer complaints. The types of apology strategies showed that both female and male front officers combined all three apology strategies which are IFIDs, Account and Positive Politeness Apology Strategies. Besides, the order of their use of apology strategies were also varied. However, the female front officers had more Positive politeness apology strategies when responding to complaints with attacks and the male front officer did not use Account strategy when handling customer complaints without attacks. Finally, it can be concluded that types of complaint play a more important role than gender factor in the use of apology strategies by these female and male front officers.